Między utopią socjalizmu a karykaturą Zachodu. Nie-dziecięca interpretacja świata przedstawionego w trylogii o skrzacie Nieumiałku Mikołaja Nosowa - Studenna-Skrukwa, Marta (Studia Europaea Gnesnensia, 2018)
This paper attempts an interpretation of Nikolai Nosov’s novels about the adventures of Dunno, which enjoyed a cult status in the Soviet Union. Despite being children’s literature, they are examined in terms of themes that have little to do with young readers. The analysis is historical rather than literary, aiming chiefly to elucidate the cultural context and the social notions from the period of Khrushchev’s thaw. Here, the author undertakes to answer the questions concerning the extent to which the reality created by Nosov served to mould the socialist worldview as early as childhood and, simultaneously, whether it incidentally offered the adult reader an opportunity of intellectual escape into the officially condemned world.